Enhancing solar photovoltaic efficiency: A computational fluid dynamics analysis - Rai, Rahool; Mangi, Fareed Hussain; Ahmed, Kashif; Sudhakar, Kumarasamy (Tech Science Press, 2024)
The growing need for sustainable energy solutions, driven by rising energy shortages, environmental concerns, and the depletion of conventional energy sources, has led to a significant focus on renewable energy. Solar energy, among the various renewable sources, is particularly appealing due to its abundant availability. However, the efficiency of commercial solar photovoltaic (PV) modules is hindered by several factors, notably their conversion efficiency, which averages around 19%. This efficiency can further decline to 10%–16% due to temperature increases during peak sunlight hours. This study investigates the cooling of PV modules by applying water to their front surface through Computational fluid dynamics (CFD). The study aimed to determine the optimal conditions for cooling the PV module by analyzing the interplay between water film thickness, Reynolds number, and their effects on temperature reduction and heat transfer. The CFD analysis revealed that the most effective cooling condition occurred with a 5 mm thick water film and a Reynolds number of 10. These specific parameters were found to maximize the heat transfer and temperature reduction efficiency. This finding is crucial for the development of practical and efficient cooling systems for PV modules, potentially leading to improved performance and longevity of solar panels. Alternative cooling fluids or advanced cooling techniques that might offer even better efficiency or practical benefits.